“We Should Be Taught Self-Respect, Self-Confidence and Self-Love”: Youth Perspectives of Adult Influences on Their Sexuality and Relationships Among South African Adolescents Living With HIV - Bergam, Scarlett; Kuo, Caroline; Atujuna, Millicent; Pellowski, Jennifer A.; Mtukushe, Bulelwa; Ndevu-Qwabe, Nontembeko; Matiwane, Mluleki; Rencken, Camerin A.; Belsky, Mikaela; Hoare, Jacqueline; Bekker, Linda-Gail; Harrison, Abigail D. (Frontiers in Reproductive Health, 2022)
Introduction Of the 1.75 million adolescents aged 10–19 years living with HIV globally, 84% reside in sub-Saharan Africa. This problem is most acute in South Africa, where there are 720,000 adolescents living with HIV (ALHIV). ALHIV navigate the same challenges as other adolescents—such as puberty and first relationships—as well as challenges specific to their HIV-status—including stigma, disclosure, and concerns about HIV transmission. This dual burden calls for tailored sexual and reproductive health (SRH) programs. Here, we qualitatively explore the reflections of South African ALHIV on SRH education, communication, and discussion provided by adults in schools, clinics, and the home related to their unique SRH needs. Methods This paper reports on qualitative data from a mixed-methods study to inform interventions that meet the SRH needs of ALHIV. In-depth interviews (N = 20) were conducted with ALHIV recruited from two clinics in Cape Town, South Africa. Nine males and 11 females aged 16–19 participated in semi-structured in-depth interviews to discuss their sexual health as ALHIV. The interview guide explored 1) perceived SRH needs; 2) healthy living with HIV; 3) future goals; 4) intimate relationships; 5) psychosocial challenges; and 6) preferred interventions. Data were thematically applied to an iteratively-developed codebook and analyzed by the cross-cultural research team using NVivo 12. Results These qualitative data reveal the pressing needs among ALHIV for open communication and accurate information about sexuality and HIV, given the risk to themselves and their partners as they enter intimate relationships. Three themes emerged from the data: 1) Intergenerational pressures coming from caregivers, clinicians, and teachers often stigmatize the sexual heath behaviors of ALHIV; 2) When present, open intergenerational communication can provide ALHIV with crucial information, resources, and social support that supports healthy decisions, and 3) ALHIV offer specific ideas about how adults can support their decision-making in the transition to adulthood. Conclusions Findings highlight adolescents' recommendations for programs involving open communication, stigma-reduction around sexuality, and support from both peer and adult mentors. This study lays the foundation for strategies to improve intergenerational communication about sexual health to promote positive approaches to sexuality for ALHIV.